UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MATEMATIS SISWA MELALUI PEMBELARAN BERBASIS IT (GEOGEBRA) - Ummu Habibah Siregar; Benny Sofyan Samosir; Wiwik Novitasari (Jurnal Karya Pendidikan Matematika, 2021)
The industrial revolution 4.0 is a formidable challenge for the world of education, one of which is learning mathematics. Moreover, in the current Covid-19 condition, which requires that learning be carried out by e-learning, the level of students' mathematical problem solving abilities is getting lower. To overcome this problem, this study applied an IT-based learning model (geogebra). The objectives of this research are to know the improvement of students' mathematical problem solving, the improvement of students' mathematical learning activities, and the improvement of the teacher's ability to manage learning. This type of research is Classroom Research. The analytical technique used is descriptive. The results of this study seen from the results of students' mathematical problem solving tests increased by 33.33%. Student activity in learning increased by 23.43%. The ability of teachers to manage learning increased by 36%. So the results of this study show that the IT-based learning model (geogebra) can improve students' mathematical problem solving, student activities in class X Multimedia I SMK Negeri 4 Padangsidimpuan.